TRACKING A SOUND SOURCE USING CORRELATION TECHNIQUES. - Berman, A.; Clay, C. S. (1958)
A simple harmonic sound source was towed in the Western North Atlantic. The signals were observed at four widely separated hydrophones. The motion of the source caused the frequency of the signal observed to be different from the source frequency by the Doppler relationship. The different frequencies were analyzed with the IBM 650. The position and the track of the source were determined. The circle of error was about 15 mi for a 15-min sample of data and it was less for longer data samples. (Author)